2018
DOI: 10.1038/s41598-018-21221-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectral features of the tunneling-induced transparency and the Autler-Townes doublet and triplet in a triple quantum dot

Abstract: We theoretically investigate the spectral features of tunneling-induced transparency (TIT) and Autler-Townes (AT) doublet and triplet in a triple-quantum-dot system. By analyzing the eigenenergy spectrum of the system Hamiltonian, we can discriminate TIT and double TIT from AT doublet and triplet, respectively. For the resonant case, the presence of the TIT does not exhibit distinguishable anticrossing in the eigenenergy spectrum in the weak-tunneling regime, while the occurrence of double anticrossings in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…After the double quantum inter-dot tunneling couplings are considered, the nonlinear response of the system is enhanced largely. [43,44] Luo et al [45,46] also confirmed that the Kerr nonlinearity of the TQD system can dramatically be enhanced compared to that of double QD system. This means that there exhibit a series of novel nonlinear properties in TQD molecule device.…”
Section: Introductionmentioning
confidence: 90%
“…After the double quantum inter-dot tunneling couplings are considered, the nonlinear response of the system is enhanced largely. [43,44] Luo et al [45,46] also confirmed that the Kerr nonlinearity of the TQD system can dramatically be enhanced compared to that of double QD system. This means that there exhibit a series of novel nonlinear properties in TQD molecule device.…”
Section: Introductionmentioning
confidence: 90%
“…The Fano resonance (FR) is an interference phenomenon widely studied in the light-matter interaction systems, which is caused by the interference between a narrow discrete resonance and a broad spectral continuum [1][2][3]. As a universal phenomenon in optics, FR with an asymmetric profile in optical response can be observed in the plasmonic nanostructures [3,4], electromagnetic metamaterials [3,5], photonic crystals [6,7], semiconductor nanostructures [8][9][10], etc. Plasmonic FR that originates from the destructive interference between the superradiant and subradiant resonance modes with a spectrum overlapping in the metallic subwavelength nanostructures has characteristics similar to the traditional FR in the interacting quantum systems [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, these interesting optical effects have attracted the scientific interest, both on an experimental, as well as on a theoretical level, in hybrid nanostructures which are composed of SQDs and MNPs [1][2][3][4][5]. The study of the Λ-type system that describes the asymmetric double-SQD system has also attracted the scientific interest of several scientists, who investigated the pump-probe response and the FWM [6,7] and as the Autler-Townes splitting and the tunneling-induced transparency [8,9]. In this work, we are interested in the study of a complex structure in which an asymmetric double-SQD molecule is coupled to an MNP.…”
Section: Introductionmentioning
confidence: 99%